Understanding safeguarding for children and their educational experiences : a guide for students, ECTs and school support staff - McGovern, William; Gillespie, Aidan; Woodley, Helen (Emerald Publishing Limited, 2022)
Many of the problem's children face in relation to their personal lives, educational experiences and attainment are caused by factors that exist outside schools. Yet despite this, all educational establishments and all school staff now have a clear 'duty' and 'responsibility' to respond to safeguarding and vulnerability concerns. All school staff are expected to be particularly alert to specific risks and the needs of children in particular groups or sets of circumstances children face in their daily living experiences. In policy documents and academic texts on safeguarding and vulnerability it is relatively easy to identify and define individuals, groups and sub-groups who are deemed to be more at risk. A key gap in the existing literature is that no consideration is given to explain and understand why children and young people find themselves in these positions of risk or vulnerability in the first place. This book fills this gap in the literature, building on current government publications, and collectively supports and compliments the endeavours of schools, universities, trainee teachers/ECTs and school support staff in relation to understanding and meeting the needs of pupils who may be at risk. This is achieved by bringing together subject area experts and academics (teaching and non-teaching) from a range of subject areas to explore three main areas: understanding the concepts of vulnerability, enhancing pupil engagement and teaching practices, and social problems, risk and resilience. This timely and accessible work will be vital reading for academic and professional teaching staff, trainee teachers and ECTs.
Keywords: Educational counseling.; Student affairs services.; Education -- Counseling -- General.; Education: care & counselling of students.; elektronické knihy; electronic books